Court Authority in Confirmation by Judicial Presumption - Dr. Fwrat Rostam Ameen Al-Jaf (International Journal of Advanced Science and Technology, 2020)
One of the most important duties of the judiciary is hearing all the parties for the proceedings and investigate all facts to form its opinion and make a fair decision in the examined case. Therefore, the parties of the proceedings must provide evidence to get their rights. Because direct evidences are often difficult to obtain, most, if not all, legislations allowed to use indirect evidences through judicial presumptions.